Literasi Keuangan, Persepsi Risiko, dan Minat Investasi Emas Digital pada Generasi Z di Kota Cirebon: Peran Mediasi Perilaku Keuangan - Fanny Annisa Fazarrosy; Krisdiana Krisdiana (Jurnal Maksipreneur, 2026)
The digital transition has broadened young individuals' access to a range of financial options, including digital gold. Nonetheless, the presence of digital platforms does not consistently correlate with substantial investment interest. This study aims to investigate the influence of financial literacy and risk perception on the inclination to invest in digital gold, both directly and indirectly through financial behavior among Generation Z in Cirebon familiar with the Pegadaian Digital service. This study employs a quantitative methodology via a cross-sectional survey design. Data were gathered from 130 participants by purposive sampling and analyzed via PLS-SEM. The findings indicate that financial literacy positively and significantly influences financial behavior and interest in investing in digital gold. Financial conduct exerts a positive and considerable influence on investment interest and mediates the impact of financial literacy on investment interest. Conversely, risk perception exerts no substantial influence on financial behavior or investment desire, and its indirect impact is likewise negligible. The findings suggest that enhancing Generation Z's interest in digital gold investment requires an emphasis on bolstering practical financial literacy and cultivating sound financial habits.